PELATIHAN MERAMU CAIRAN PEMBASMI JENTIK NYAMUK DARI DAUN SIRIH (Piper betle L.) DI DESA TIBUBIU KECAMATAN KERAMBITAN TABANAN - Sukadana, I M.; Santi, Sri Rahayu; Bogoriani, N. W. (Buletin Udayana Mengabdi, 2012)
The Community Service activity about the manner of making natural mosquito antilarvae liquids from Piper betle L leaf was conducted on the 24st of October 2010 to the mothers of PKK of Tibubiu village, Kerambitan subdistrict, Tabanan district. Making natural mosquito antilarvae liquids from Piper betle L leaf used the simple formulation technique. The liquids were made by using petroleum as a solvent and Piper betle L leaf as a antilarvae agent. The result of this activity and evaluation showed that the mosquito antilarvae liquids product is as good as chemical agent like “abate”. All participants showed enthusiastic during the activity and they will try to make these liquids. All participants, moreover understand about making liquids and they want to try at home. Such public service is interesting to because the peoples have improved knowledge, skill, and possibility to open of new entrepreneur in village so that it can be vacancy and increase income to community.